Meningitis in der Notaufnahme - Regner-Nelke, Liesa; Ruck, Tobias; Meuth, Sven G. (AINS - Anästhesiologie · Intensivmedizin · Notfallmedizin · Schmerztherapie, 2023)
Meningitis describes an inflammation of the meninges of the brain and spinal cord, which, depending on the etiology, can be a serious disease with high lethality. The suspicion of meningitis therefore requires rapid and adept action. In this paper, we explain the diagnostic and therapeutic approach to suspected meningitis in the emergency department.
Keywords: Meningitis; Meningismus; Meningokokken; Kopfschmerzen; Vigilanzminderung